A guardian role of TagA in protecting Mycobacterium tuberculosis from nitrosative killing - Ying Zhang; Hao Wang; Yatong Liu; Ziyao Qin; Yawen He; Hui-Ling Wang; Xuejiao Huang; Jianhui Li; Shiqi Xie; Shaoqiong Huang; Zeyu Huang; Xiang Cheng; et al. (Proceedings of the National Academy of Sciences, 2026)
Upon activation, macrophages generate substantial levels of reactive nitrogen species, which can induce alkylating damage in the DNA of intracellular Mycobacterium tuberculosis ( Mtb ) and thereby restrict bacterial replication. However, the molecular mechanisms by which Mtb repairs such DNA lesions remain poorly understood. Here, we identified genes required for Mtb survival in distinct macrophage subsets using transposon insertion sequencing. Among these, tagA displayed a specialized role in Mtb survival in M1-polarized macrophages, as well as in mice at 4 wk postinfection, a stage when macrophages are biased toward an M1-polarized state. Mechanistically, TagA conferred resistance to the DNA alkylating agent methyl methanesulfonate through its 3-methyladenine (3-MA) excision activity with Glu48 serving as a key catalytic residue for substrate binding. Critically, TagA was found to protect the Mtb genome from alkylation damage caused by nitrosative stress—a hallmark of the M1-polarized macrophage microenvironment. Furthermore, pharmacological inhibition of inducible nitric oxide synthase (iNOS) with S-methylisothiourea sulfate in mice or genetic deletion of nos2a in zebrafish markedly rescued the survival defect of Δ tagA . Together, these findings reveal a previously unappreciated mechanism by which the DNA repair enzyme TagA protects Mtb against 3-MA DNA damage under nitrosative stress, thereby promoting bacterial survival in M1-polarized macrophages and during in vivo infection.